Belowground biomass harvest influences biomass production, stock, export and nutrient use efficiency of second rotation Eucalyptus plantations - Kulmann, Matheus Severo de Souza; Eufrade-Junior, Humberto de Jesus [UNESP]; Dick, Grasiele; Schumacher, Mauro Valdir; de Azevedo, Gileno Brito; Azevedo, Glauce Taís de Oliveira Sousa; Guerra, Saulo Philipe Sebastião [UNESP] (Elsevier, 2022)
Forest residues from Eucalyptus plantations, including the belowground biomass, has become an important energy source in tropical countries. However, the belowground biomass harvesting may reduce wood productivity in the subsequent rotations due to the depletion of soil nutrients. Thus, the present study aimed to evaluate the nutritional sustainability of Eucalyptus clones’ plantations grown on second rotation in different above and belowground biomass harvest scenarios. Second rotation clones were used: Eucalyptus urophylla (AEC 0144); Eucalyptus urophylla × E. grandis (H77); and Eucalyptus urophylla × E. camaldulensis (VM01) at 13.1, 12.9 and 12.0 years of age, respectively. Trees were uprooted and split into leaves, branches, bark, stemwood and belowground. Biomass production, concentration, stock, export and use efficiency of N, P, K, Ca, Mg, B, Cu, Fe, Mn and Zn were evaluated. The highest belowground biomass production occurred in the VM01 clone, while AEC 0144 clone had the highest production of stemwood biomass. Stemwood and belowground biomass fractions had the lowest nutrient concentrations. The highest concentrations of nutrients were verified in leaves, branches and bark. Stemwood and stemwood with belowground biomass harvest scenarios presented the lowest nutrient export values and highest NUE values. Our results demonstrate that woody production of belowground biomass represents a significant part of the total biomass production of Eucalyptus trees. Thus, the removal of leaves, branches and bark fractions is more harmful to the nutritional sustainability of sandy soils than the harvesting of stumps in second rotation plantations.
Keywords: Biomass production; Eucalypt; Forest residue management; Harvest scenario; NUE; Stock nutrient